Bosna i Hercegovina od početka procesa disolucije SFRJ do međunarodnog priznanja / Bosnia and Herzegovina in the Process from SFRJ Yugoslavia Dissolution to the International Recognition - Šehić, Zijad (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
In the paper author analyzes, by using referential sources and literature, crucial events and processes that affected happenings in Bosnia and Herzegovina from the beginning of SFR Yugoslavia‟s dissolution to the international recognition of Bosnia and Herzegovina on 6 April 1992. The special attention is devoted to the situation in internal BH political scene by emphasizing the national goals and means of their achievement.